Training load and recovery in volleyball during a competitive season - Andrade, D. M.; Fernandes, G.; Miranda, R.; Coimbra, D. R.; Bara Filho, M. G. (The Journal of Strength and Conditioning Research, 2021)
The objective of this study was to analyze the training load (TL) and recovery status (RS) of a volleyball team in different periods of the season. Fifteen male athletes participated in the study. Training load was quantified through the rate of perceived exertion of session. The total weekly TL of the preparatory period (PP), competitive period I (CPI), and competitive period II (CPII) was calculated. Total quality recovery was used to evaluate the initial and final RS. Training load was higher (p < 0.05) in PP than in CPI and CPII. The final RS was lower (p < 0.05) in PP than in CPI and CPII. There was a difference (p < 0.05) between the initial and final RS in the analyzed periods. An inverse correlation (p: -0.62) was observed between the TL and the initial and final difference RS in PP. In conclusion, PP in volleyball presented the highest TL, related to a greater difference between the initial and final RS.